LEARNING PROGRAM ADMINISTRATION IMPLEMENTATION IN EDUCATION - Makmur Syukri; Amiruddin Amiruddin (Universitas Negeri Medan, 2019)
Abstract: Administration of learning programs is an activity that includes setting a set of learning experience programs arranged to develop students' abilities in accordance with school goals in order to create an effective and efficient teaching and learning process. Program evaluation is a series of activities carried out intentionally to see success rates program. Through program evaluation, the evaluation step is not only carried out haphazardly but is systematic, detailed, and uses procedures that have been carefully tested. Keywords: Administration, Learning Program Abstrak: Administrasi program pembelajaran merupakan kegiatan yang meliputi pengaturan seperangkat program pengalaman belajar yang di susun untuk mengembangkan kemampuam siswa sesuai dengan tujuan sekolah dalam rangka terciptanya proses belajar mengajar yang efektif dan efisien. Evaluasi program adalah suatu rangkaian kegiatan yang dilakukan dengan sengaja untuk melihat tingkat keberhasilan program. Dengan melalui evaluasi program, langkah evaluasi bukan hanya dilakukan serampangan saja tetapi sistematis, rinci, dan menggunkan prosedur yang sudah diuji secara cermat. Kata Kunci: Administrasi, Program Pembelajaran